1954
DOI: 10.1042/bj0580622
|View full text |Cite
|
Sign up to set email alerts
|

A study of the metabolism of phosphorus in mammalian red cells

Abstract: were made. All species of spermatozoa tested, including those highly sensitive-to an increase in osmotic pressure, were fully motile in 20M glycerol. It is most unlikely that cells impermeable to glycerol would retain motility in the presence of such an excessive external osmotic pressure, and the retention of motility in the presence of high concentrations of glycerol was taken as evidence that the cells were permeated by this solute. Other neutral solutes can to some extent protect spermatozoa against damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0
1

Year Published

1957
1957
1982
1982

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(59 citation statements)
references
References 20 publications
5
53
0
1
Order By: Relevance
“…Prankerd and Altman (1954) observed that adenosine was more effective than glucose as a substrate for glyceraldehyde-3-phosphate formation in human erythrocytes. They suggested this was because adenosine had an ATPsparing effect and provided purine for ATP synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…Prankerd and Altman (1954) observed that adenosine was more effective than glucose as a substrate for glyceraldehyde-3-phosphate formation in human erythrocytes. They suggested this was because adenosine had an ATPsparing effect and provided purine for ATP synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…Phosphate esters were separated and analysed by methods described by Prankerd and Altman (20), and their specific activities estimated. No difference was found between normal and digoxin-treated (5 ug./ml.)…”
Section: The Lack Of Influence Of Digoxin On Cell Phosphate Esters Anmentioning
confidence: 99%
“…Some investigators have reported changes in red cell membrane permeability to Na+ and K+ following cholinesterase inhibition (Greig, Faulkner & Mayberry, 1953;Holland & Greig, 1950;Ludwig, Greig & Peterson, 1951) and in addition, considerable evidence has been presented indicating that the permeability of the cell membrane is dependent on cell metabolism (Bartlett & Marlow, 1953;Danowski, 1941;Dawson & Widdas, 1963;Gabrio, Finch & Huennekens, 1956 ; Harris, 1941 ;Jacob & Jandl, 1962b ; Prankerd, 1955 ;Prankerd & Altman, 1954). In view of these relationships, it was of interest to investigate the possibility of an alteration of cell metabolism by an anticholinesterase compound.…”
Section: Introductionmentioning
confidence: 99%